(3NQjOI GdbUQ hLQjOI GdYUQs - (3eMeO Hf eMeO MGeO GdCUHgGfj, YeGO GdOjf GdcGJH,J (B597 (3g` s
(3ChdgG (B:s
(3PcQ eMGSf GdaVdGA HGdHdGO GdTGejI hGdaQGJjI hGdLRjQI s
(3BNQgG (B:s
(3jfJgi HJQLeI CHj Ydi GdMSjf Hf YHO Gddg Hf QhGMI GdNehi Hbhdg (B: (3hGSJTgO GHf QhGMI GdePchQ ai GdeYScQ GdUdGMi Je GdLRA GdSGOS s
(3jJVef GdLRA GdChd ef GdbSe GdKGdK ai JQGLe TYQGA GdTGe hGdaQGJ hGdLRjQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B26s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs